Glycogen replacement rate and its use in program design - Treffene, B.
This paper connects the glycogen recovery time to the set up of fast and slow work within a weekly program. This enables race pace work in a program throughout the training season. Results: At a very slow swimming speed only the red slow twitch fibres will be used (mainly fat metabolism). Near the anaerobic threshold (AT) the heart rate will be 40-60bpm lower than maximum and red ST fibres will utilise carbohydrate (glycogen) as well as fat. At speeds near but below the critical speed (given as a time for 100m [Tcr]) the FT red fibres increase their utilisation with the production of lactic acid, which will stabilise (maybe with a slow rise with time) at a large value for sprinters and lower values for distance swimmers. For speeds above Tcr, which are 400m and below swimming racing speeds the white FT fibres are coupled into the force production in increasing numbers or firing rates.